Documented atrial fibrillation recurrences after pulmonary vein isolation are associated with diminished quality of life. Issue 3 (March 2016) - Berger, Wouter R.; Krul, Sébastien P.J.; van der Pol, Joy A.; van Dessel, Pascal F.H.M.; Conrath, Chantal E.; Wilde, Arthur A.M.; de Groot, Joris R.
Abstract : Aims: Pulmonary vein isolation (PVI) aims at eliminating symptomatic atrial fibrillation. In this regard, the most relevant indication for this procedure is the reduction of symptoms and improvement of quality of life (QoL) in patients who remain symptomatic despite antiarrhythmic drug treatment. We investigated the relation between documented atrial fibrillation recurrences and QoL in patients after PVI. Methods: One hundred and six PVIs were performed in 99 patients. Follow-up was mainly performed at referring hospitals. Short Form 36 (SF-36) QoL questionnaires were completed before and 1 year after PVI. Electrocardiographic recordings from the first postprocedural year were retrospectively collected, 3 months blanking excluded. Atrial fibrillation recurrence was defined as any recurrence of atrial arrhythmia documented on ECG or 24-h-Holter. Results: Before PVI, patients had lower QoL than the general Dutch population in 7/8 SF-36 questionnaire subscales (sumQoL 419.4 ± 161 vs. 617.9, P  < 0.001). Atrial fibrillation recurred in 52 (49%) patients. In these patients, four subscales increased following PVI (physical functioning P  < 0.001, role physical P  = 0.006, bodily pain P  = 0.011 and social functioning P  = 0.047). SumQoL remained lower than the general Dutch population (546.7 ± 157, P  = 0.003). In patients without documented recurrences, QoL improved to a level similar to that of the general Dutch population (602.9 ± 148; P  = 0.46). The number of electrocardiographic recordings was lower in the group without documented recurrences (2.5 ± 1.8 vs. 3.8 ± 1.7, P  = 0.002). Conclusion: In patients without documentation of atrial fibrillation, QoL increased up to the level of the general population after PVI, but it remained lower in patients with recurrences. In the latter group more ECGs were done, suggesting that QoL relates particularly to symptomatic episodes. Improvement of QoL is therefore an important attribute of PVI.